Evolutionary mechanisms of deep-seated toppling deformation of rock slope under different free-face conditions - Zheng, Da; Pan, Yuanyang; Wang, Qinyuan; Zhou, Hang; Zheng, Haijun; Li, Dan (Environmental earth sciences, 2023)
Toppling deformation is a unique geological form in rock slopes, with complex geomechanical behavior and engineering properties. A large number of deep-seated toppling deformation slopes are developed in the deep incised valleys in Southwest China. By summarizing these typical slope cases, it is found that there are certain differences in the rock mass strength, stratigraphic lithology, thickness and dip angle of rock strata. However, the slope angle of these slopes is relatively close. This finding shows that the free surface conditions are the key factors for the formation of deep-seated toppling deformation slopes. To further verify this preliminary conclusion, taking the toppling deformation body before the dam of the Lancang River Gushui hydropower station in Southwest China as a research object, this paper analyzes the basic characteristics of deep-seated toppling deformation of rock slopes. By analyzing the formation conditions, combined with the indoor centrifuge model test, the evolution process of the deep-seated toppling deformation of the anti-dip rock slope under hydropower engineering excavation conditions was simulated. The influence law of varied the free-face conditions on the deep-seated toppling deformation of slope was revealed. The results demonstrate that the free-face conditions of the slope have a significant impact on the deep-seated toppling deformation. The study area was subject to the continuous and rapid downcutting of the Lancang River, which led to the formation of the free face on both banks of the rock mass and further triggered the deep-seated toppling deformation of the slope under the condition of gravity. According to the three excavation tests of centrifuge model, it can be found that the catastrophic process of deep-seated toppling and deformation of the anti-dip rock slope can be summarized as follows: rock strata are toppling and bending—cracks appear in the rock mass—cracks are connected to form bending zones—multi-level bending zones are formed—the rock body is sheared and destabilized along a certain level of bending zones. Centrifuge model test has good applicability for the study of the deformation evolution process of rock slope.